Reliable space‐to‐Earth communication as a secondary service in the 460–470 MHz band. (26th February 2014) - Gunther, Jacob; Fish, Chad; Swenson, Charles; Moon, Todd
Summary By regulatory fiat, secondary communication services cannot cause harmful interference to primary communication services, and they cannot claim protection from harmful interference from the primary service. This paper is about establishing reliable high data rate space‐to‐Earth communication in the asymmetric setting of a secondary service in the 460–470 MHz frequency band. In this band, the primary services consist of signals that are narrowband relative to the bandwidth of the signal of interest. A frequency domain approach is adopted to detect and cancel narrowband interference. After this processing, the signal of interest can be demodulated by standard techniques. This approach is shown to be effective on real data collected for the Dynamic Ionosphere CubeSat Experiment mission. The telemetry concept for Dynamic Ionosphere CubeSat Experiment was developed with a view toward demonstrating a high‐speed data downlink capability that may be adopted as a standard for future CubeSat missions. Copyright © 2014 John Wiley & Sons, Ltd.